Clinical characteristics and treatment of infantile Takayasu arteritis in the Chinese Han population: a single-center study - Jia Zhu; Min Kang; Yingjie Xu; Dan Zhang; Tong Yue; Ming Li; Min Wen; Feifei Wu; Gaixiu Su; Yang Yang; Wenquan Niu; Jianming Lai (Pediatric Rheumatology Online Journal)
Abstract Objectives This study aims to summarize and explore the clinical characteristics, treatment strategies, and follow-up outcomes of infantile Takayasu arteritis (TA) in the Chinese Han population. Methods In this retrospective study, we collected clinical data, Kerr scores (the NIH score), and arterial involvement scores (AIS) of infants diagnosed with TA at the time of initial diagnosis and at 1, 3, 6, and 12 months following initial treatment. Prognostic differences between various treatment groups were also analyzed. Results A total of 18 Chinese Han infants with TA were included. The average age of onset was 85.06 ± 54.64 days. The main clinical manifestations included fever (77.78%) and hypertension (55.56%). Both the erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels were elevated above normal. The average Kerr score was 3.28 ± 0.67, and the AIS was 10.67 ± 4.30. The most commonly affected arteries were the coronary arteries (72.22%) and the abdominal aorta (72.22%), with arterial wall thickening present in all patients (100%). All patients were initially diagnosed with bacterial infections, and 16 were specifically diagnosed with Kawasaki disease empirically. Ten patients received infliximab treatment, and eight were treated with tocilizumab. At 6 months post-treatment, both the AIS and Kerr scores showed significant improvement compared to initial values (t = 2.469, p = 0.019; t = 12.369, p = 0.000). No deaths occurred during the 12-month follow-up. No significant differences were observed between the tocilizumab and infliximab treatment groups. Conclusion ITA is primarily characterized by fever and hypertension, along with elevated inflammatory biomarkers. The condition is easily diagnosed empirically with bacterial infections and Kawasaki disease, particularly in female infants around 3 months of age. Arterial involvement is often extensive and severe. Aggressive treatment within the first six months after diagnosis can significantly improve clinical outcomes. Both infliximab and tocilizumab demonstrated effective control of arterial inflammation.